Health Insurance Literacy and Roles for Reference Librarian Involvement. Issue 2 (3rd April 2017) - Vardell, Emily; Charbonneau, Deborah H.
ABSTRACT: The role of librarians in addressing health insurance information needs emerged following a request from President Barack Obama for librarians to assist the public with navigating the Affordable Care Act and the Health Insurance Marketplace. The goal of this article is to highlight a number of concrete ways reference work could be expanded, especially in public library settings, to support health insurance literacy concerns by offering illustrative examples and recommendations for authoritative health insurance information resources. Overall, this article contributes to the existing literature by offering practical recommendations that may be relevant to reference librarians supporting the health insurance information needs of their communities.